Glacial history of the European marine mussels Mytilus, inferred from distribution of mitochondrial DNA lineages - Śmietanka, B (Heredity (Edinb), 2014)
Mussels of the genus Mytilus have been used to assess the circumglacial phylogeography of the intertidal zone. These mussels are representative components of the intertidal zone and have rapidly evolving mitochondrial DNA, suitable for high resolution phylogeographic analyses. In Europe, the three Mytilus species currently share mitochondrial haplotypes, owing to the cases of extensive genetic introgression. Genetic diversity of Mytilus edulis, Mytilus trossulus and Mytilus galloprovincialis was studied using a 900-bp long part of the most variable fragment of the control region from one of their two mitochondrial genomes. To this end, 985 specimens were sampled along the European coasts, at sites ranging from the Black Sea to the White Sea. The relevant DNA fragments were amplified, sequenced and analyzed. Contrary to the earlier findings, our coalescence and nested cladistics results show that only a single M. edulis glacial refugium existed in the Atlantic. Despite that, the species survived the glaciation retaining much of its diversity. Unsurprisingly, M. galloprovincialis survived in the Mediterranean Sea. In a relatively short time period, around the climatic optimum at 10 ky ago, the species underwent rapid expansion coupled with population differentiation. Following the expansion, further contemporary gene flow between populations was limited.